INVESTIGATING ENGLISH PRONUNCIATION CHALLENGES AMONG THE DAYAK KANAYANT EFL PRE-SERVICE TEACHERS - Rische, Veggi; Nurcahyoko, Kunto; Siboro, Efrika (STKIP Persada Khatulistiwa Sintang, 2025)
This study investigates the pronunciation challenges of Dayak Kanayant EFL pre-service teachers and strategies to mitigate such challenges. The present study employed a mixed methods approach. There were 10 pre-service teachers who participated in the study. For the quantitative data, the participants were asked to do voice recordings of 30 English words to identify patterns of pronunciation errors. To generate the qualitative data, in-depth interviews were conducted with participants to explore the strategies they used to overcome pronunciation challenges. Three primary categories of pronunciation problems were identified: complicated errors (6.7%), vowel errors (41%), and consonant faults (52.3%). Vowel errors frequently entailed replacing English vowels with Dayak Kanayant phonetic system-related sounds, while consonant errors included replacing /f/ and /v/ with /p/ and /b/ since these sounds are not present in their mother tongue. Consonant clusters and silent letters were among the complex errors. Participants used a variety of strategies to overcome these obstacles, such as technology-based resources (including YouTube and Google Translate), peer feedback, mimicking and repeating native speakers, and heightened awareness of how their original accent affects how they pronounce English. The study emphasizes the significance of comprehending the phonetic distinctions between the Dayak Kanayant language and English, and it recommends that pre-service teachers employ focused techniques to enhance their pronunciation.